Assessment of the implantation of proyect based learning as a tool for the study of business economics (Journal of Management and Business Education, 2018)
This investigation describes an experience carried out at the students of Business Administration. This experience has consisted of combining Project Based Learning and the use of new Information and Communication Technologies (ICT). The project has consisted of the creation of didactic videos, carried out by students. Videos have basic content on business fundamentals. Our aim has been to motivate students to learn under the multiple possibilities and advantages of ICT and also to encourage them to have autonomous learning for the development of new video creation tools, as well as the use of the YouTube social network. This has been used, in this case, for teaching and learning. A group of students developed resources that have allowed us to improve the learning experience of the rest of the students. We have achieved a more innovative learning for the students and their ability to create short, useful, dynamic and creative videos themselves. In addition, we have also achieved an increased the student motivation. We have also achieved competencies such as: ICT management, organizational and planning skills, information management, decision making, reinforcement of teamwork, collaborative learning, in addition, students obtain specific competences.
Keywords: Teaching innovation; Project-Based Learning; collaborative learning; YouTube; teaching videos